PENERAPAN FORECASTING MENGGUNAKAN METODE SINGLE EXPONENTIAL SMOOTHING DAN TREND MOMENT DALAM MEMPREDIKSI PENJUALAN ALAT-ALAT OUTDOOR PADA EIGHTVENTURE - Darmin (IONTech Journal, 2024)
Eightventure is one of Tokopedia's partners that sells a variety of outdoor equipment. In 3 years running, sales of outdoor equipment have fluctuated, which of course the increase and decrease in sales every month is difficult to predict. The problem that often arises in eigthventure is the occurrence of stock mismatches, this is because there are products that are not sold out and there are some products that many consumers ask for but are not fulfilled. With this problem, Eightventure must be able to predict how many products will be sold and how many products must be provided. On the other hand, the sales report data generated in Tokopedia has never been used because of the limitations of the Eightventure in processing the data, so that it is difficult to predict sales. Therefore, a research was carried out using the Single Exponential Smoothing and Trend Moment methods and to measure the level of prediction accuracy, the mean absolute deviation, mean squared error, root mean squared error and mean absolute percentage error were used. With these two methods, the results of research on sales predictions for the double layer dome tent product with a capacity of 6 BN 021 shows that the single exponential smoothing method results in mean absolute deviation 1.31, mean squared error 3.28, root mean squared error 1.81, and mean absolute percentage error of 35%. While the trend moment method obtained the mean absolute deviation 1.28, mean squared error 2.35, root mean squared error 1.53, and mean absolute percentage error 39%. Therefore, it can be noticed that the trend moment method is the most effective in calculating the eightventure sales forecast. Keywords : Sales, Single Exponential Smoohting, Trend Moment.